An Analysis Of Politeness Strategies Used By Donald Trump And Hillary Clinton Presidential Debate 2016 - Muhammad Hasyimsyah Batubara; Cut Dara Ilfa Rahila; Hamna Fitri (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
Politeness is usually related to speech acts done by the speaker, and this can be seen in everyday life when people are having a conversation. The conversation that we often see in video debate is a conversation that has the value of politeness. This research analyzes politeness introduced by Brown and Levinson in Donald Trump and Hillary Clinton's presidential debate 2016. This research used a qualitative approach with library research. The sources of data were primary and secondary data. The data were in source primary the form of utterances that contain politeness strategies. Donald Trump and Hillary Clinton's presidential debate 2016 script was the data source. Secondary data in this research is the politeness aspect related to the problem in this research. The collecting data techniques are reduction, display, verification, or drawing conclusion. The result of the analysis is bald on record (16), positive politeness (26), negative politeness (34), and off-record (10). So the total politeness that occurred in Donald Trump and Hillary Clinton's presidential debate in 2016 is 86. The dominant utterance varieties politeness in presidential debate 2016 is 34 negative politeness.